2019
DOI: 10.3389/fonc.2019.01444
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Cell-in-Cell Formation in Heterogeneous Human Breast Cancer Tissue in a Patient With Poor Prognosis: A Case Report and Literature Review

Abstract: Cell cannibalism is a unique pathological phenomenon that has been observed at low frequency in a variety of human tumor samples (<0.5%), including breast cancer. Cannibalistic cells typically form cell-in-cell (CIC) structures characterized by enclosure of one cell or more by another, mediating a novel type of cell death "entosis," which was proposed as the type IV cell death. A large number of CIC structures are generally associated with malignant transformation and progression, and they are believed to be p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…Further development of the model could allow for more variety in choosing the cell size, as well as for introducing additional cell lines to a heterogeneous tumor. Empirical data confirm that heterogeneous tumors indeed consist of various cells (Al-Brahim & Salama, 2005;Gerlinger et al, 2012;Stanta & Bonin, 2018), and that the cell size is important in cancer growth and propagation (Grichnik et al, 2006;Rosai, 2011;Lyons et al, 2016). Our model can help to explain that the cell size, in addition to other e.g., mechanical parameters (Sarna et al, 2018), may give the answer.…”
Section: Opportunitiessupporting
confidence: 60%
See 1 more Smart Citation
“…Further development of the model could allow for more variety in choosing the cell size, as well as for introducing additional cell lines to a heterogeneous tumor. Empirical data confirm that heterogeneous tumors indeed consist of various cells (Al-Brahim & Salama, 2005;Gerlinger et al, 2012;Stanta & Bonin, 2018), and that the cell size is important in cancer growth and propagation (Grichnik et al, 2006;Rosai, 2011;Lyons et al, 2016). Our model can help to explain that the cell size, in addition to other e.g., mechanical parameters (Sarna et al, 2018), may give the answer.…”
Section: Opportunitiessupporting
confidence: 60%
“…One of the simplest distinguishing features of a cell is its size. It is a well-known fact that the growth and the propagation of cancer vary depending on the cell size (Li & Lowengrub, 2014;Li et al, 2015;Schmoller, 2017), and that the size of the cells in a heterogeneous tumor differs (Sastre-Garau et al, 2004;Ruan et al, 2019;Xu et al, 2020). Therefore indeed, the cell size may be a good starting point for analyzing the cell population heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…One study revealed the poor outcome and disease recurrence of lung adenocarcinomas, associated with an increased number of entotic structures [ 28 ]. In the case report of one patient with invasive ductal carcinoma, a high frequency of entotic figures was accompanied by poor prognosis [ 30 ].…”
Section: Entosis In Cancermentioning
confidence: 99%
“…Cell-in-cell (CIC) is an evolutionarily conserved cytobiological phenomenon ( 1 , 2 ), which was first reported 150 years ago by a German scholar ( 3 ). It refers to the presence of one or more living cells within another living one and has ever since been found in varieties of tumors tissues, such as breast carcinoma ( 4 , 5 ), pancreatic ductal adenocarcinoma ( 6 ), and head and neck squamous cell carcinoma (HNSCC) ( 7 ) and the like. CIC has two typical forms: one is homotypic CIC, and the other is heterotypic CIC, with the latter often occurring between tumor cells and immune cells that include neutrophils ( 8 ).…”
Section: Introductionmentioning
confidence: 99%